Microwave-assisted synthesis of NaYF4:Yb3+/Tm3+ upconversion particles with tailored morphology and phase for the design of UV/NIR-active NaYF4:Yb3+/Tm3+@TiO2 core@shell photocatalysts - Ullah, Sajjad [UNESP]; Hazra, Chanchal [UNESP]; Ferreira-Neto, Elias P.; Silva, Tárcio C. [UNESP]; Rodrigues-Filho, Ubirajara P.; Ribeiro, Sidney J. L. [UNESP] (Royal Society of Chemistry (RSC), 2017)
Coupling of TiO2 with rare earth (RE) metal-based upconversion particles (UCPs) is a promising strategy to develop near-infrared (NIR)-driven TiO2-based photocatalysts. This, however, requires the controlled synthesis of bright NIR-to-UV UCPs with tailored morphology, size and crystalline phase. Herein, we report a rapid, efficient and reproducible co-precipitation/microwave (MW)-assisted hydrothermal method for the preparation of NaYF4:Yb3+/Tm3+ UCPs which allows tailoring the morphology (spherical nanoparticles, microrods) and crystalline phase (cubic, hexagonal) and hence the optical response of the resulting UCPs by simply varying the MW treatment time or ethylenediaminetetraacetic acid (EDTA) concentration. The EDTA concentration strongly affects the size of the primary UCPs during the co-precipitation step which plays a decisive role in dictating the final particle morphology in the subsequent MW-assisted hydrothermal step. Based on microscopic and XRD analyses, a model for the growth of UCPs with different morphologies has been proposed. Pure hexagonal microrods with strong upconversion (UC) photoluminescence (PL) in the UV (345 nm, 361 nm) and visible (450 nm, 475 nm) regions are obtained using MW treatment times of 30-60 min and EDTA/RE3+ molar ratios above 1.5. The UCPs@TiO2 core@shell composite photocatalysts prepared by coating anatase TiO2 on the surface of UCPs using a sol-gel method showed good photocatalytic activity under both ultraviolet (UV) and NIR light. This efficient and reproducible co-precipitation/MW-assisted approach may be considered as a step forward towards the efficient harvesting of sunlight for photochemical and photoelectrical applications based on TiO2.